Answer:192 because id u do the math and multiply.
2x-4=3-x +1
<span>Simplifying
2x + -4 = 3 + -1x + 1
Reorder the terms:
-4 + 2x = 3 + -1x + 1
Reorder the terms:
-4 + 2x = 3 + 1 + -1x
Combine like terms: 3 + 1 = 4
-4 + 2x = 4 + -1x
Solving
-4 + 2x = 4 + -1x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add 'x' to each side of the equation.
-4 + 2x + x = 4 + -1x + x
Combine like terms: 2x + x = 3x
-4 + 3x = 4 + -1x + x
Combine like terms: -1x + x = 0
-4 + 3x = 4 + 0
-4 + 3x = 4
Add '4' to each side of the equation.
-4 + 4 + 3x = 4 + 4
Combine like terms: -4 + 4 = 0
0 + 3x = 4 + 4
3x = 4 + 4
Combine like terms: 4 + 4 = 8
3x = 8
Divide each side by '3'.
x = 2.666666667
Simplifying
x = 2.666666667</span>
Possible if they dont have to pay on the same months
Answer: D
Step-by-step explanation:
It’s really obvious just circle D
About 151. That seems pretty close. If it is incorrect, sorry.